Smeed's law and expected road fatality reduction: An assessment of the Italian case. (December 2015) - Persia, Luca; Gigli, Roberto; Usami, Davide Shingo
Abstract: Introduction: Smeed's law defines the functional relationship existing between the fatality rate and the motorization rate. While focusing on the Italian case and based on the Smeed's law, the study assesses the possibility for Italy of reaching the target of halving the number of road fatalities by 2020, in light of the evolving socio-economic situation. Method: A Smeed's model has been calibrated based on the recorded Italian data. The evolution of the two indicators, fatality and motorization rates, has been estimated using the predictions of the main parameters (population, fleet size and fatalities). Those trends have been compared with the natural decreasing trend derived from the Smeed's law. Results: Nine scenarios have been developed showing the relationship between the fatality rate and the motorization rate. In case of a limited increase (logistic regression) of the vehicle fleet and according to the estimated evolution of the population, the path defined by motorization and fatality rate is very steep, diverging from the estimated confidence interval of the Smeed's model. In these scenarios the motorization rate is almost constant during the decade. Conclusions: In the actual economic context, a limited development of the vehicle fleet is more plausible. In these conditions the target achievement of halving the number of fatalities in Italy may occur only in case of a structural break (i.e., the introduction of highly effective road safety policies). Practical application: The proposed tools can be used both to evaluate retrospectively the effectiveness of road safety improvements and to assess if a relevant effort is needed to reach the established road safety targets. Highlights: We applied Smeed's formula to the Italian case study. We examine the future evolution of fatality rate in Italy under different scenarios. Vehicle fleet growing according to Gompertz model is needed to meet the Smeed's law. In the most reliable scenario Smeed's law is not met without a structural break.